PELATIHAN EDUKASIONAL TENTANG PEMANFAATAN BIJI CHIA SEBAGAI NUTRISI TAMBAHAN UNTUK IBU HAMIL KEPADA KADER DESA TUAH NEGERI - Uthia, Rahimatul; Susanti, Ari (EBIMA : Jurnal Edukasi Bidan di Masyarakat, 2022)
The prevalence of stunting toddlers increased in 2017 from 27.5% to 29.6%. Stunting occurs from the pre-conception mother who is malnourished and anemic and becomes severe during pregnancy with insufficient nutritional intake. Chia seeds as a food ingredient were safe because it has no side effects or allergenicity. Thus, chia seeds and their derivative products are a promising source for development. Chia seeds contain 17.83% omega-three fatty acids (-linolenic acid), sources of dietary fiber, a protein with high biological value, and antioxidants. In addition to containing essential fatty acids, chia seeds contain phenolic compounds. These phenolic compounds are bioactive components that contribute to the health benefits of chia seeds. However, this time, many studies on the chemical content of Chia seeds made us interested to see a different effects of Chia seeds, such a have a significant effect on fetal growth. This information is not widely known by the public yet. So the solution offered is to educate the people of Tuah Negeri Village, Tenayan Raya Pekanbaru District utilize these chia seeds as additional nutrition for pregnant women. Keywords: chia seeds, fetus, PMT Keywords: chia seeds, fetus, PMT